Systematic review and meta-analysis of prognostic models in Southeast Asian populations with acute myocardial infarction - Ismail, Sophia Rasheeqa; Khalil, Muhamad Khairul Nazrin; Mohamad, Mohd Shawal Faizal; Azhar Shah, Shamsul (Frontiers in Cardiovascular Medicine, 2022)
Background: The cultural and genetic diversity of the Southeast Asian population has contributed to distinct cardiovascular disease risks, incidence, and prognosis compared to the Western population. Thereby raising concerns about the accuracy of predicted risks of existing prognostic models. Objectives: We aimed to evaluate the predictive performances of validated, recalibrated, and developed prognostic risk prediction tools used in the Southeast Asian population with acute myocardial infarction (AMI) events for secondary events Methods: We searched MEDLINE and Cochrane Central databases up to March 2022. We included prospective and retrospective cohort studies that exclusively evaluated populations in the Southeast Asian region with a confirmed diagnosis of an AMI event and evaluated for risk of secondary events such as mortality, recurrent AMI, and heart failure admission. The CHARMS and PRISMA checklists and PROBAST for risk of bias assessment were used in this review. Results: We included 7 studies with 11 external validations, 3 recalibrations, and 3 new models from 4 countries. Both short- and long-term outcomes were assessed. Overall, we observed that the external validation studies provided a good predictive accuracy of the models in the respective populations. The pooled estimate of the C-statistic in the Southeast Asian population for GRACE risk score is 0.83 (95%CI 0.72 – 0.90, n=6 validations) and for TIMI risk score is 0.80 (95%CI: 0.772 – 0.83, n=5 validations). Recalibrated and new models demonstrated marginal improvements in discriminative However, the method of predictive accuracy measurement in most studies was insufficient thereby contributing to the mixed accuracy effect. The evidence synthesis was limited due to the relatively low quality and heterogeneity of the available studies. Conclusion: Both TIMI and GRACE risk scores demonstrated good predictive accuracies in the population. However, with the limited strength of evidence, these results should be interpreted with caution. Future higher-quality studies spanning various parts of the Asian region will help to understand the prognostic utility of these models better.